The Effect of Internal Control Unit And Implementation of Internal Control on The Achievement Good University Governance - Roni Budianto; Rama Komara Putra; Windu Mulyasari (Jurnal Riset Akuntansi Terpadu, 2021)
This study aims to determine the influence of the role of the internal supervision unit and the application of internal control towards the achievement of good university governance. Respondents in this study were 85 auditors who worked in the Internal Control Unit at State Universities in the Jakarta, Bogor, Depok, Tangerang, and Serang areas.This study uses primary data and questionnaires to obtain information from respondents using the purposive sampling method. SmartPLS version 3 was used in this study to analyze research consisting of descriptive statistics and hypothesis testing.The results. The results of this study indicate that the role of the internal control unit and the implementation of internal controls have a positive and significant effect on achieving good university governance.